THE VIEW OF THE MEDAN CITY OF ISLAMIC ASSEMBLY ON THE PROFESSION OF WIFE AS MALE MASSAGERS: Case Study of Kampung Baru Village, Medan Maimun District - Intan Lubis; Abdurrahim Abdurrahim (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: This study aims to explain the views of the Medan City Islamic Ulema Council on the Profession of Wives as Male Masseurs in the village of Kampung Baru, Medan Maimun District. The method used in this study is a qualitative descriptive method. The technique used in data collection is interviews. Data analysis was carried out through the inductive method, which is a method that studies a specific phenomenon to obtain the rules that apply in the field that are more general about the phenomenon being investigated. This method is used in making conclusions about various matters regarding the MUI's view of the wife's profession as a male masseur. The findings of the study indicate that the Indonesian Ulema Council (MUI) views women as male masseurs in law, with the provisions (i) maintaining modesty in both dress and behavior so as not to cause lust for the masseur and the massaged; (ii) there are more than two people in the massage room to avoid sexual harassment or other forms of adultery; and (iii) it is intended as a medical and exercise treatment. Keywords: Views of the Islamic Ulema Council (MUI), Wife, Masseur, Profession